2018
DOI: 10.1194/jlr.r082503
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid transfer protein: its impact on lipoprotein homeostasis and atherosclerosis

Abstract: Phospholipid transfer protein (PLTP) is one of the major modulators of lipoprotein metabolism and atherosclerosis development in humans; however, we still do not quite understand the mechanisms. In mouse models, PLTP overexpression induces atherosclerosis, while its deficiency reduces it. Thus, mouse models were used to explore the mechanisms. In this review, I summarize the major progress made in the PLTP research field and emphasize its impact on lipoprotein metabolism and atherosclerosis, as well as its reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 109 publications
2
22
0
Order By: Relevance
“…In addition to isolating APOA1-HDL, enrichment of PLTP-containing HDL particles may be necessary to detect APOA1 transfer from alpha2 to alpha1 and alpha0. It is also possible that PLTP’s primary function on HDL in plasma is not its phospholipid transfer activity, which is localized to its minor alpha2 size ( 30 , 39 ), but instead a currently unidentified function in alpha0 and alpha1 ( 41 ). Alpha0 and alpha1 contain the majority of PLTP mass on HDL (60%) and a higher ratio of PLTP per particle (1 molecule of PLTP for every 20 and 50 particles of alpha0 and alpha1, respectively), compared with alpha2 (36% of total PLTP mass on HDL, 1 molecule of PLTP for every 500 alpha2 particles).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to isolating APOA1-HDL, enrichment of PLTP-containing HDL particles may be necessary to detect APOA1 transfer from alpha2 to alpha1 and alpha0. It is also possible that PLTP’s primary function on HDL in plasma is not its phospholipid transfer activity, which is localized to its minor alpha2 size ( 30 , 39 ), but instead a currently unidentified function in alpha0 and alpha1 ( 41 ). Alpha0 and alpha1 contain the majority of PLTP mass on HDL (60%) and a higher ratio of PLTP per particle (1 molecule of PLTP for every 20 and 50 particles of alpha0 and alpha1, respectively), compared with alpha2 (36% of total PLTP mass on HDL, 1 molecule of PLTP for every 500 alpha2 particles).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effect of PLTP inhibition on RCT is currently controversial. 5 It has been suggested that just increasing the total amounts of HDL would not directly lead to the treatment of dyslipidemia and cardiovascular diseases. 22,23 Therefore, we postulate that investigation using PLTP inhibitors with a higher affinity and inhibitory activity may resolve the issue of whether a change of HDL metabolism by PLTP inhibition would contribute to the treatment of the above-mentioned diseases.…”
Section: Discussionmentioning
confidence: 99%
“…4 PLTP is ubiquitously expressed in animal cells and tissues with higher expression in macrophages and atherosclerotic lesions, and its expression in the liver accounts for around 25% of all plasma PLTP activity. 5 Its expression can be regulated by transcription factors such as peroxisome proliferator-activated receptor, 6 farnesoid X receptor, 7 liver X receptor, 8,9 and sterol regulatory element-binding protein 1c, 10 which are involved in lipid synthesis, lipoprotein production, and reverse cholesterol transport (RCT). In addition, a hyperlipidemia mouse model induced by a high-fat, high-cholesterol diet exhibited a significant increase in PLTP expression and activity.…”
Section: Introductionmentioning
confidence: 99%
“…FFA taken up by the liver could also be re-esterified into triglycerides. While we did not find liver triglyceride levels to be different, the increased abundance of Pltp mRNA in sedentary and exercised vitamin-E fed mice may be of interest in this context; Pltp is a vitamin E transfer protein and is also important for the lipidation and hepatic secretion of VLDL [ 34 ]. Thus, the vitamin E-supplemented mice may not have accumulated hepatic triglycerides due to increased VLDL release.…”
Section: Discussionmentioning
confidence: 99%